2021
DOI: 10.1002/adfm.202101438
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Interface in FAPbI3 Planar Perovskite Solar Cells by Imidazole‐Graphene‐Quantum‐Dots

Abstract: Organic–inorganic hybrid perovskites have reached an unprecedented high efficiency in photovoltaic applications, which makes the commercialization of perovskite solar cells (PSCs) possible. In the past several years, particular attention has been paid to the stability of PSC devices, which is a critical issue for becoming a practical photovoltaic technology. In particular, the interface‐induced degradation of perovskites should be the dominant factor causing poor stability. Here, imidazole bromide functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 31 publications
(33 reference statements)
0
54
0
Order By: Relevance
“…Moreover, a better energy level alignment between ETL and perovskite can be obtained. [51] Overall, carbon materials and derivatives can enhance the conductivity very well to improve charge transfer. Likewise, it can passivate interface defects and regulate energy level alignment, and the formation of perovskite films.…”
Section: Carbon-based Inorganic Materialsmentioning
confidence: 99%
“…Moreover, a better energy level alignment between ETL and perovskite can be obtained. [51] Overall, carbon materials and derivatives can enhance the conductivity very well to improve charge transfer. Likewise, it can passivate interface defects and regulate energy level alignment, and the formation of perovskite films.…”
Section: Carbon-based Inorganic Materialsmentioning
confidence: 99%
“…For example, Gao et al demonstrated that imidazole bromide‐functionalized graphene quantum dots (I‐GQD) could adjust the lower interface between the ETL and the FAPbI 3 perovskite layer. [ 120 ] On the one hand, I‐GQDs eliminated the surface defects of SnO 2 ETL, achieved better energy‐level alignment between ETL and perovskite to enhance carrier transfer, and inhibited interface charge recombination to reduce voltage loss. On the other hand, the multifunctional groups on the surface of I‐GQDs helped the growth of the FAPbI 3 perovskite film, leading to larger grain size, lower trap density, and longer carrier lifetime, but without remarkable change of the perovskite bandgap ( Figure ).…”
Section: Optimization Of Device Structure and Interface Layersmentioning
confidence: 99%
“…Recently, QDs research aimed at developing good quality QDs for solar cell and biomedical devices and applications [24][25][26][27][28][29][30]. Each application requires unique parameters to Carbon-QDs emit photons that spans from the ultraviolet to infrared energy, at a variance of semiconductor counterpart the photoluminescence comes from different oxidation of graphene that introduced discrete energy levels [19] achieve a good detection limit, such as excitation energy, emission wavelength and yield.…”
Section: Sustainable Qds and Its Application In Solar Cellsmentioning
confidence: 99%